Impact of 5-aminolevulinic acid with iron supplementation on exercise efficiency and home-based walking training achievement in older women - Masuki, Shizue; Morita, Atsumi; Kamijo, Yoshi-ichiro; Ikegawa, Shigeki; Kataoka, Yufuko; Ogawa, Yu; Sumiyoshi, Eri; Takahashi, Kiwamu; Tanaka, Tohru; Nakajima, Motowo; Nose, Hiroshi (Journal of applied physiology (1985), 2016)
A reduction in exercise efficiency with aging limits daily living activities. We examined whether 5-aminolevulinic acid (ALA) with sodium ferrous citrate (SFC) increased exercise efficiency and voluntary achievement of interval walking training (IWT) in older women. Ten women [65 ± 3(SD) yr] who had performed IWT for >12 mo and were currently performing IWT participated in this study. The study was conducted in a placebo-controlled, double-blind crossover design. All subjects underwent two trials for 7 days each in which they performed IWT with ALA+SFC (100 and 115 mg/day, respectively) or placebo supplement intake (CNT), intermittently with a 2-wk washout period. Before and after each trial, subjects underwent a graded cycling test at 27.0°C atmospheric temperature and 50% relative humidity, and oxygen consumption rate, carbon dioxide production rate, and lactate concentration in plasma were measured. Furthermore, for the first 6 days of each trial, exercise intensity for IWT was measured by accelerometry. We found that, in the ALA+SFC trial, oxygen consumption rate and carbon dioxide production rate during graded cycling decreased by 12% ( P < 0.001) and 11% ( P = 0.001) at every workload, respectively, accompanied by a 16% reduction in lactate concentration in plasma ( P < 0.001), although all remained unchanged in the CNT trial ( P > 0.2). All of the reductions were significantly greater in the ALA+SFC than the CNT trial ( P < 0.05). Furthermore, the training days, impulse, and time at fast walking were 42% ( P = 0.028), 102% ( P = 0.027), and 69% ( P = 0.039) higher during the ALA+SFC than the CNT intake period, respectively. Thus ALA+SFC supplementation augmented exercise efficiency and thereby improved IWT achievement in older women.